2013
DOI: 10.1111/php.12118
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Effect on the Photocrosslinking Reaction between 3‐Cyanovinylcarbazole Nucleoside and Pyrimidine Base in DNA/RNA Heteroduplex

Abstract: To clarify the geometric effect of the ultra-fast photocrosslinking reaction of photoreactive oligodeoxyribonucleotide containing 3-cyanovinylcarbazole nucleoside ((CNV)K) on uridine in complementary RNA strands, pseudouridine (Ψ), which is an isomer of uridine with a C5-C1' glycosidic bond, was introduced to the photocrosslink site of (CNV)K in complementary RNA instead of U. The photoreactivity of (CNV)K toward Ψ was two-fold lower than that of U, suggesting that the geometry between the vinyl moiety on (CNV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In 2008, as the other class of photoreactive moiety for DNA photo-cross-linking, we successfully developed an artificial nucleoside that has a 3-cyanovinylcarbazole moiety instead of nucleobase ( CNV K). The oligodeoxyribonucleotide-containing CNV K can photo-cross-link to a pyrimidine base at the −1 position in complementary DNA or RNA within a few seconds of photoirradiation. This quick photo-cross-linking reaction is applicable for antisense strategy, selection of miRNAs, and construction and/or stabilization of nanostructured DNA. Thus, we believe that CNV K has tremendous potential for biological and nanotechnological applications; however, details of the photo-cross-linking reaction, such as the cis – trans isomeric effect of the cyanovinyl group on CNV K, are still unclear. In the previous study, HPLC analysis after the photo-cross-linking reaction gave a single peak having the molecular mass of an oligonucleotide photodimer, suggesting strongly that the reaction occurred through either one of the cis or trans isomers of CNV K …”
Section: Introductionmentioning
confidence: 99%
“…In 2008, as the other class of photoreactive moiety for DNA photo-cross-linking, we successfully developed an artificial nucleoside that has a 3-cyanovinylcarbazole moiety instead of nucleobase ( CNV K). The oligodeoxyribonucleotide-containing CNV K can photo-cross-link to a pyrimidine base at the −1 position in complementary DNA or RNA within a few seconds of photoirradiation. This quick photo-cross-linking reaction is applicable for antisense strategy, selection of miRNAs, and construction and/or stabilization of nanostructured DNA. Thus, we believe that CNV K has tremendous potential for biological and nanotechnological applications; however, details of the photo-cross-linking reaction, such as the cis – trans isomeric effect of the cyanovinyl group on CNV K, are still unclear. In the previous study, HPLC analysis after the photo-cross-linking reaction gave a single peak having the molecular mass of an oligonucleotide photodimer, suggesting strongly that the reaction occurred through either one of the cis or trans isomers of CNV K …”
Section: Introductionmentioning
confidence: 99%
“…5-methylcytosine plays a crucial role in the tissue-specific gene expression pattern, the inactivation of X-chromosome activity, and genomic imprinting [131][132][133]. The 5-methyl uracil used for the photochemistry as the probe has a potency of antimicrobial activity [134][135][136][137][138]. Reactions of 5-substitution for pyrimidine have been developed based on the C-H activation, palladium coupling reaction, and the addition of formaldehyde [8,139,140].…”
Section: Synthesis Of C5-methylpyrimidinementioning
confidence: 99%
“…Various photo-cross-linkers, e.g., psoralen, coumarin, and diazirine, , which can cross-link with the nucleobase on the complementary strand, have been developed and applied for regulating gene expression and RISC functions, and for constructing DNA nanostructures. As another class of DNA photo-cross-linker, we previously reported 3-cyanovinylcarbazole nucleoside ( CNV K; Scheme ) with an ultrafast photo-cross-linking manner . Since oligodeoxyribonucleotides (ODN(s)) having CNV K can photo-cross-link with the pyrimidine base in the complementary DNA or RNA possessed at the −1 position of CNV K via [2 + 2] photocycloaddition reaction within a few seconds of 366 nm irradiation, CNV K has wide potential for regulating nucleic acid functions without photodamage to cells , and for constructing DNA-based thermally stable nanostructures. In our previous report, we tried to clear the mechanism of the photoreaction from the viewpoint of the structure of the photo-cross-linked product and also the geometry of the vinyl group of CNV K and the C5–C6 double bond of the target pyrimidine base; however, the effect of the local stability of the base paring of the target pyrimidine has not been evaluated. Most recently, we found that the CNV K analogue having d -threoninol instead of 2′-deoxyribose has higher photoreactivity compared to CNV K .…”
Section: Introductionmentioning
confidence: 99%
“…16 Since oligodeoxyribonucleotides (ODN(s)) having CNV K can photo-crosslink with the pyrimidine base in the complementary DNA or RNA possessed at the −1 position of CNV K via [2 + 2] photocycloaddition reaction within a few seconds of 366 nm irradiation, CNV K has wide potential for regulating nucleic acid functions without photodamage to cells 17,18 and for constructing DNA-based thermally stable nanostructures. 19−21 In our previous report, we tried to clear the mechanism of the photoreaction from the viewpoint of the structure of the photocross-linked product 22 and also the geometry of the vinyl group of CNV K and the C5−C6 double bond of the target pyrimidine base; 23 however, the effect of the local stability of the base paring of the target pyrimidine has not been evaluated. Most recently, we found that the CNV K analogue having D-threoninol instead of 2′-deoxyribose has higher photoreactivity compared to CNV K. 24 As the D-threoninol skeleton has higher flexibility compared to the 2′-deoxyribose skeleton, the photoreactivity of 3-cyanovinylcarbazole might largely depend on the stability and/or the flexibility of the structure around the reaction point, i.e., vinyl group on 3-cyanovinylcarbazole moiety and C5−C6 double bond on the target pyrimidine base.…”
Section: ■ Introductionmentioning
confidence: 99%